Descriptive study of the challenges when implementing an app for patients with neovascular age-related macular degeneration to monitor their vision at home - Chris A Rogers; Andrew Lotery; Tunde Peto; Sobha Sivaprasad; Barnaby C Reeves; Michael Donnelly; Ruth E Hogg; E Ward; Ben J L Burton; Paul C Knox; Charlene Treanor; Seán R O’Connor; et al. (BMJ Open)
Objectives Remote monitoring of health has the potential to reduce the burden to patients of face-to-face appointments and make healthcare more efficient. Apps are available for patients to self-monitor vision at home, for example, to detect reactivation of age-related macular degeneration (AMD). Describing the challenges when implementing apps for self-monitoring of vision at home was an objective of the MONARCH study to evaluate two vision-monitoring apps on an iPod Touch (Multibit and MyVisionTrack).Design Diagnostic Test Accuracy study.Setting Six UK hospitals.Methods The study provides an example of the real-world implementation of such apps across health sectors in an older population. Challenges described include the following: (1) frequency and reason for incoming calls made to a helpline and outgoing calls made to participants; (2) frequency and duration of events responsible for the tests being unavailable; and (3) other technical and logistical challenges.Results Patients (n=297) in the study were familiar with technology; 252/296 (85%) had internet at home and 197/296 (67%) had used a smartphone. Nevertheless, 141 (46%) called the study helpline, more often than anticipated. Of 435 reasons for calling, all but 42 (10%) related to testing with the apps or hardware, which contributed to reduced adherence. The team made at least one call to 133 patients (44%) to investigate why data had not been transmitted. Multibit and MyVisionTrack apps were unavailable for 15 and 30 of 1318 testing days for reasons which were the responsibility of the app providers. Researchers also experienced technical challenges with a multiple device management system. Logistical challenges included regulations for transporting lithium-ion batteries and malfunctioning chargers.Conclusions Implementation of similar technologies should incorporate a well-resourced helpline and build in additional training time for participants and troubleshooting time for staff. There should also be robust evidence that chosen technologies are fit for the intended purpose.Trial registration number ISRCTN79058224.